A Note on Discrete Multitime Recurrences of Samuelson-Hicks Type. (25th October 2016) - Pansera, Bruno Antonio; Strati, Francesco
Abstract : By this work, we aim at fostering further research on the applications of multitime recurrences. In particular, we shall apply this method by generalizing the Samuelson-Hicks model so as to make the new concept of time that this method proposes clear. In particular, the multitime approach decomposes a point of time into a vector, taking into account how different coordinates of time referring to the same date can affect the dynamics of a model.